Hypertensive disorders of pregnancy and the risk of anxiety disorders in adolescence: Findings from the Avon Longitudinal Study of Parents and Children - Dachew, B.; Scott, J.; Mamun, A.; Alati, Rosa (2019)
© 2019 Elsevier Ltd Background: The effect of hypertensive disorders of pregnancy (HDP) on offspring anxiety disorders in adolescence is not yet known. This study aims to examine the association between HDP and offspring anxiety disorders at age 15 years. Methods: We used data from 5231 mother–offspring pairs from the United Kingdom based Avon Longitudinal Study of Parents and Children (ALSPAC). Anxiety disorder was diagnosed in the offspring at the age of 15 years using the Development and Well-Being Assessment (DAWBA). Results: Among those who had anxiety disorders, 16.4% were exposed to HDP. After adjusting for a wide range of known confounders, we found that adolescents of women with HDP had a 2.43 fold (95% CI: 1.41–4.19) increase risk of anxiety disorders compared with adolescents of women without HDP. Conclusions: Our study showed that adolescents exposed to HDP had higher risk of anxiety disorders compared with unexposed adolescents and suggests that prevention and treatment of maternal HDP could possibly prevent offspring anxiety in adolescence. Early screening for anxiety disorders in offspring of women with HDP may also be warranted. Further research is needed to explain the pathways by which HDP may increase the risk of offspring psychopathology.